2010
DOI: 10.1038/nnano.2010.44
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes degraded by neutrophil myeloperoxidase induce less pulmonary inflammation

Abstract: We have shown previously that single-walled carbon nanotubes can be catalytically biodegraded over several weeks by the plant-derived enzyme, horseradish peroxidase. However, whether peroxidase intermediates generated inside human cells or biofluids are involved in the biodegradation of carbon nanotubes has not been explored. Here, we show that hypochlorite and reactive radical intermediates of the human neutrophil enzyme myeloperoxidase catalyse the biodegradation of single-walled carbon nanotubes in vitro, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
735
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 726 publications
(798 citation statements)
references
References 29 publications
38
735
2
4
Order By: Relevance
“…There have been suggestions that CNTs can undergo a degree of dissolution depending on their form 42,43 ; thus, the retention/translocation kinetics of long CNTs from the pleural space could change over time if the CNTs undergo any biodissolution. Recently, Tomatis et al 44 reported that the greater toxicity of long asbestos fibers when compared with short asbestos fibers could be attributed to several factors other than length, including greater free radical production and reactive surface.…”
Section: Discussionmentioning
confidence: 99%
“…There have been suggestions that CNTs can undergo a degree of dissolution depending on their form 42,43 ; thus, the retention/translocation kinetics of long CNTs from the pleural space could change over time if the CNTs undergo any biodissolution. Recently, Tomatis et al 44 reported that the greater toxicity of long asbestos fibers when compared with short asbestos fibers could be attributed to several factors other than length, including greater free radical production and reactive surface.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been discovered that CNTs could be metabolized by neutrophil myeloperoxidase [6] and the functionalized CNTs (f-CNTs) have less cytoxicity [7]. In the past 10 years, a variety of f-CNTs including oxidized, aminated, surfactant-assisted dispersed, polymer-assisted dispersed, and bio-molecular modified CNTs have been discovered [8] and utilized as the effective bio-molecular carriers to deliver peptides, proteins, nucleic acids and small molecular drugs into cellular systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, polystyrene has been shown to be resistant to thermal oxidation below 200°C, which is far above the viability limit of in vitro biological conditions. [37][38][39] A high level of lysosomal accumulation was associated with a low level of cytokine signalling 24 h post exposure of the BBB monolayer to 100 nm PS COOH NPs. Inflammasome activation due to lysosome signalling is associated with an increase in activated IL1-beta levels, which were not found in this study.…”
Section: Discussionmentioning
confidence: 99%